Power sharing control of batteries within autonomous microgrids based on their state of charge - Hosseinimehr, T.; Shahnia, Farhad; Ghosh, A. (2015)
This paper presents a new power sharing approach among parallel battery storage systems within an autonomous microgrid. The proposed approach considers the state of charge (SoC) of the batteries to control the ratio of their output powers. To facilitate this, a new SoC-based droop control is proposed. In this method, the ratio of output power for all the batteries is determined as a function of their SoC level. This ratio will be varied over time. In order to make the output power of each storage unit independent from the SoC level of the rest of storage units, a modified droop-based voltage control technique is applied for the other energy resources of the microgrid. By the help of the modified control system, the output power reduction of batteries is only picked up by the energy resources. The studies and discussions are validated through PSCAD/EMTDC simulation studies.